2018
DOI: 10.2147/ott.s164574
|View full text |Cite
|
Sign up to set email alerts
|

Adenosquamous carcinoma of the lung

Abstract: Adenosquamous carcinoma of the lung (ASC), a relatively rare subtype of non-small-cell lung cancer, is defined as a malignancy containing components of lung adenocarcinoma (ADC) and lung squamous cell carcinoma (SCC). Although ASC has biological characteristics of ADC and SCC, it is not by any means a simple hybrid of two components above. It is extremely difficult to diagnose preoperatively; pathology of surgically resected gross specimen is the most effective means for adequate diagnosis of ASC. Platinum-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 57 publications
1
75
0
3
Order By: Relevance
“…Besides, lung ASC had higher grade malignancy, stronger lymph nodal invasiveness, more frequent brain metastases and poorer prognosis than lung adenocarcinoma (ADC) and SCC [12]. However, in other studies, there were also ASC in some site behaved similar with common type.…”
Section: Discussionmentioning
confidence: 82%
“…Besides, lung ASC had higher grade malignancy, stronger lymph nodal invasiveness, more frequent brain metastases and poorer prognosis than lung adenocarcinoma (ADC) and SCC [12]. However, in other studies, there were also ASC in some site behaved similar with common type.…”
Section: Discussionmentioning
confidence: 82%
“…In 1978, the Japanese Lung Cancer Society reported that to be able to diagnose ASC, components of SCC and adenocarcinoma have to constitute 20% of each tumor [15]. In the last WHO classification, it is required for each component to form 10% of the tumor [16]. Pleomorphic, fusiform cell and giant cell carcinomas constitute less than 3% of lung cancers [11].…”
Section: Discussionmentioning
confidence: 99%
“…However, since some COSMIC cases precede this classification, we will still use the term bronchioalveolar in this report. Squamous cell carcinoma and adenosquamous carcinoma are the two other forms of lung cancer [25] reported on COSMIC. "Non-small cell carcinoma" refers to non-classified NSCLC or unknown origin.…”
Section: Classificationmentioning
confidence: 99%